Shahjahanama : Inayat Khan's Account - Dossal, Zubeida A.; Illustrated By Haider, Masroor (Karachi Oxford University Press, 2009)
The Historical Readers series is a supplementary text for secondary and upper secondary classes which aims to develop students$1 (Binterest in the history of the region. Drawing from authentic Mughal sources,the diaries and accounts of personal as well as court life,maintained by the rulers, their children,and court officials, give readers a fascinating glimpse into the life and times of a dynasty that ruled the subcontinent for over 300 years. Abridged and simpli?ed,the books have been attractively illustrated in a style that matches their mood and content.s
Include Illustrations.
Keywords: India--Mogul Empire -- Shahjahan, Emperor of India, Approximately 1592-1666 -- Kings and Rulers